Mission and conversion proselytizing in the religious history of the Roman Empire - Goodman, Martin (Clarendon Press, 1994)
Much of the book focusses on the history of Judaism in late antiquity. Dr Goodman makes a detailed and radical re-evaluation of the evidence for Jewish missionary attitudes in the late Second Temple and Talmudic periods, questioning many commonly held assumptions, in particular the view that Jews proselytized energetically in the first century CE. This leads him on to take issue with the common notion that the early Christian mission to the gentiles imitated or competed with contemporary Jews. Finally, the author puts forward some novel suggestions as to how the Jewish background to Christianity may nonetheless have contributed to the enthusiastic adoption of universal proselytizing by some followers of Jesus in the apostolic age